Survey of the risk behaviors and mental health of adolescents in Gabon - Joel Fleury Djoba Siawaya; Steeve Minto’o Rogombe; Mah Diawara; Rotimi Myrabelle Avome Houechenou; Nora Sylvana Efire Emagha; Zena Andrews; Lydie Armelle Moukambi; Anicet Christel Maloupazoa Siawaya; Amandine Mveang Nzoghe; Ofilia Mvoundza Ndjindji; Patrick Douada Mouguiama (Communications Medicine)
Abstract Background Adolescence shapes adulthood and is a time of vulnerability. This study explores risk behaviors among African adolescents from Gabon. Methods This study was done in 2021 and followed the Global School-Based Student Health Survey (GSHS) guidelines. Six core modules (alcohol, tobacco, and drug use, sexual behaviors, mental health, and safety) were included. A self-administered questionnaire was used to gather data. The data were analyzed using Prism version 6 GraphPad software. Results This study includes 1009 adolescents aged 10–19 years (62% females and 38% males). 30.8% are under 16 years old. 41.3% have low to medium self-esteem. The prevalence of alcohol, tobacco, and cannabis use is 37%, 7.4%, and 4.3%, respectively. 15.4% of under 16 years are alcohol drinkers. 38% are sexually active (6% of them have had sexually transmitted diseases (STDs)). Alcohol increases by 6.1 (p < 0.0001) the odds of being sexually active. The age of the first sexual intercourse is 15.3 ± 1.9 years. Sexually active adolescents have, on average, 3.2 ± 2.2 sex partners. Also, 38% of sexually active adolescents experienced coerced sex. 11.3% of sexually active girls had an abortion, and 17.4% of them had kids. 19.4% have experienced sex under substance influence. Less than half of adolescents consistently use condoms. The odds of unprotected sex under the influence of alcohol or drugs is 10.7 (p < 0.001). Conclusions These results suggest Gabonese adolescents have a relatively high rate of alcohol use, risky sexual behaviors, sexual coercion, low to medium self-esteem, and vulnerability.”